Kinematic comparison of two-legged vs. one-legged jumping in college-aged men - Chen, A.; Croftchik, T.; Hurst, P.
Our purpose was to determine whether two-legged jumping achieved a greater height than one-legged jumping. The final results showed that the two-legged jump achieved a height (1.70 m) that was 9.6% higher than that of the one-legged jump (1.55 m). These results agreed with our original expectations. Hip and knee flexion at the beginning of the jump was the key component in determining the height achieved in the jumping motion. Despite having to move the trunk a greater distance in the propulsion phase (due the deeper squat caused by the more flexed hip and knee), the subject reached the ascension phase quicker in the two-legged jump (0.165 s) than in the one-legged jump (0.231 s). More muscle force was generated in the two-legged jump compared to the one-legged jump, due to the fact that more muscles were recruited in both legs. Hip angular velocity peaked at 511 deg/s in the two-legged jump versus 346 deg/s in the one-legged jump, resulting in a higher linear hip velocity, 4.03 m/s (two-legged) versus 3.06 m/s (one-legged). Therefore, the linear hip velocity was a major determinant for the vertical height achieved. Due to the fact that both jumps had all relevant factors remaining constant (time of movement, and acceleration due to gravity), the initial velocity dictated the height of each jump (vertical displacement = vit + 1/2 at2). The results of our study were satisfactory to us. However, further analysis of other factors that affect the jumping motion would be beneficial to the experiment. For example, due to the large horizontal displacement that occurs when running and jumping off of one leg, the approach of the one-legged jumping motion was eliminated. By doing so, we compromised the true ability of the subject to reach his peak jump height. Another limitation of our study came as a result of being allowed to only focus on one joint, which we took as the hip. However, if we were able to analyze another joint, we would analyze the knee and see if angular and linear velocity of the knee joint had a pattern similar to that of the hip joint. After a more complete analysis of each movement, we would redo the experiment with no restrictions, enabling us to analyze multiple subjects performing fully functional jumps. This new data would help identify patterns of movement that would either help or hinder the jumping results and enable us to make a more real world comparison of both jumps.